THE IMPACT OF USING INSTAGRAM SOCIAL MEDIA ON STUDENT CONSUMPTIVE BEHAVIOR - Anwar, Rully Khairul; Sjoraida, Diah Fatma; Khadijah, Ute Lies Siti; Rahman, M. Taufiq (Record and Library Journal, 2020)
Background of the study: The online shop is a process of buying and selling transactions conducted by the public through the internet media. We don't have to leave the house, people can have the items they want through an online shop. The use of the internet by students cannot be separated, including using in consumption patterns through online shops. The existence of the development of telecommunications technology, online shop currently makes it easy for students to make transactions or market products, goods and services. They are not only consumers, but also online shop business people.Purpose: This study aims to determine the impact of the use of Instagram on consumptive behavior of Islam-based students in Bandung.Method: This qualitative research uses a descriptive method by taking a location on an Islamic-based campus in Bandung.Findings: There is a rationalization behind the use of Instagram of female students, in addition it was also found that female students use Instagram mainly for the improvement and adjustment of lifestyle with trending topics, especially the style of the artist. For those who have more money, the students also make online transactions to buy clothes they like.Conclusion: 1) Instagram is a phenomenal social media among female college students because users are spoiled with various features available on Instagram, 2) the campus provides a large bandwidth so they can access Instagram more easily, and 3) the impact of expanding access to the internet becomes they are more consumptive to do transactions face to face.